REALLY RETHINKING 'FORMAL METHODS.'. - Parnas, David Lorge (Computer (00189162), 2010)
The article provides comments to an article in the September issue of "Computer" magazine entitled, "Rethinking Formal Methods." The writer examines the comparable progress made in formal methods to investigate program design errors seen in 1967 which can still be found in modern day software. He suggests questioning assumptions behind formal methods for software development to know its problems and create alternatives. He observes three alarming gaps in software development which need hard rethinking rather more money to address the problems.